Change in Parent-Identified Goals in Young Children with Cerebral Palsy Receiving a Context-Focused Intervention: Associations with Child, Goal and Intervention Factors. (1st February 2014) - Pollock, Nancy; Sharma, Nicole; Christenson, Cheryl; Law, Mary; Gorter, Jan Willem; Darrah, Johanna
ABSTRACT The purpose of this study was to examine the relationship between goal achievement measured by the Canadian Occupational Performance Measure (COPM) and child, goal, and intervention factors. Participants were 41 preschool children with cerebral palsy (CP) who were in the context-focused therapy arm of a randomized controlled trial. Factors including child age, Gross Motor Function Classification System (GMFCS) level, type and complexity of goals, and intervention strategies were analyzed. Children made large, positive mean changes on the COPM over 6 months (Performance = 3.8, SD = 1.9; Satisfaction = 4.3, SD 4.3) with younger children showing greater change. The COPM scores had low to moderate correlations with change on the Pediatric Evaluation of Disability Inventory and the Gross Motor Function Measure (GMFM-66). Regression analysis indicated that age, but not GMFCS level influenced COPM change scores. Goal complexity and intervention strategies were not significantly related to COPM change scores. The results provide support for using the COPM as an individualized measure of change in young children with CP receiving intervention.